Diagnosis and screening of diabetes - Shaw, Jonathan (Henry Stewart Talks, 2013)
Define glucose levels for diabetes diagnosis, Retinopathy and glycaemia, Limitations of glucose measurement, Limitations of HbA1c measurement, Screening for diabetes with questionnaires